2022
DOI: 10.1590/1414-431x2022e12145
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine pretreatment alleviates cerebral ischemia/reperfusion injury by inhibiting neuroinflammation through the JAK2/STAT3 pathway

Abstract: Dexmedetomidine (DEX) is known to provide neuroprotection against cerebral ischemia and reperfusion injury (CIRI), but the exact mechanisms remain unclear. This study was conducted to investigate whether DEX pretreatment conferred neuroprotection against CIRI by inhibiting neuroinflammation through the JAK2/STAT3 signaling pathway. Middle cerebral artery occlusion (MCAO) was performed to establish a cerebral ischemia/reperfusion (I/R) model. Specific-pathogen-free male Sprague-Dawley rats were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It was reported that Dex could attenuate neuronal injury induced by cerebral ischemia-reperfusion by regulating miR-199a [ 9 ]. Dex pretreatment alleviated cerebral ischemia/reperfusion injury by inhibiting neuroinflammation through the JAK2/STAT3 pathway [ 8 ]. However, the specific targeting molecule has not been unfolded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that Dex could attenuate neuronal injury induced by cerebral ischemia-reperfusion by regulating miR-199a [ 9 ]. Dex pretreatment alleviated cerebral ischemia/reperfusion injury by inhibiting neuroinflammation through the JAK2/STAT3 pathway [ 8 ]. However, the specific targeting molecule has not been unfolded.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine (Dex) is a highly selective α2-adrenergic receptor agonist, with central anti sympathetic effect, can produce sedative, analgesic, and anti-anxiety effects [ 8 , 9 ]. Dex has no obvious inhibitory effect on respiration, and it is widely used in clinical practice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo JAK2 and MAPK7 mutations closely associated with ASD have been identified using whole-exome sequencing in Chinese children and adolescent trio samples ( 50 ). Negative regulation of the JAK2/STAT3 signaling pathway can inhibit neuroinflammation ( 51 ). The JAK2/STAT3 signaling pathway regulates microglia/macrophage polarization (toward M2 polarization) during cerebral ischemia reperfusion injury (CIRI), thereby attenuating brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…It was approved for sedation and analgesia in intensive care unit (ICU) patients in the United States in 1999 ( Damian et al, 2020 ). Preclinical studies have shown that DEX can improve IRI in various tissues, including the liver, thus providing organ protection ( Tang et al, 2020 ; Yu et al, 2020 ; Liu et al, 2022 ; Tao et al, 2022 ). However, its effectiveness and safety in IRI of transplanted livers still lack definite conclusions.…”
Section: Introductionmentioning
confidence: 99%